Telenursing terhadap Interdialytic Weight Gain dan Kualitas Pelayanan Keperawatan Hemodialisa - Wulandari Wulandari; Agusta Dian Ellina (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the effect of telenursing on interdialytic weight gain and the quality of hemodialysis nursing services. The research method used is experimental with a pre-test-post-test control group design. The results showed that the mean score of interdialytic weight gain in the intervention group was higher than the control group after being given the intervention, with a grand mean of 3.7. The p-value obtained was 0.000 at <0.05. The mean score of hemodialysis nursing service quality in the intervention group was higher than the control group after the intervention, with a grand mean of 13.9. The p-value obtained is 0.000 at < 0.05. In conclusion, telenursing is effective on interdialytic weight gain and the quality of hemodialysis nursing services. Keywords: Interdialytic Weight Gain, Service Quality, Telenursing